Effect of matrix stiffness on osteoblast functionalization. (15th February 2017) - Zhang, Tao; Lin, Shiyu; Shao, Xiaoru; Zhang, Qi; Xue, Changyue; Zhang, Shu; Lin, Yunfeng; Zhu, Bofeng; Cai, Xiaoxiao
Abstract: Objectives: Stiffness of bone tissue differs response to its physiological or pathological status, such as osteoporosis or osteosclerosis. Consequently, the function of cells residing in bone tissue including osteoblasts (OBs), osteoclasts and osteocytes will be affected. However, to the best of our knowledge, the detailed mechanism of how extracellular matrix stiffness affects OB function remains unclear. Materials and methods: We conducted a study that exposed rat primary OBs to polydimethylsiloxane substrates with varied stiffness to investigate the alterations of cell morphology, osteoblastic differentiation and its potential mechanism in mechanotransduction. Results: Distinctive differences of cell shapes and vinculin expression in rat osteoblasts were detected on different PDMS substrates. As representatives for OB function, expression of alkaline phosphatase, Runx2 and osteocalcin were identified and showed a decrease trend as substrates become soft, which is associated with the Rho/ROCK signalling pathway. Conclusions: Our results indicated substrate elasticity as a potent regulator in OBs functionalization, which may pave a way for further understanding of bone diseases as well as a potential therapeutic alternative in tissue regeneration.